PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) DALAM MENINGKATKAN KETERAMPILAN SOSIAL SISWA DI SEKOLAH DASAR - Sephia Ningsih, Tari; Syahrul Rizal, Muhammad; Ananda, Rizki; Yandri Kusuma, Yanti; Hana Pebriana, Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low social skills of students in class V at SDN 002 Laggini. This research aims to improve students' social skills by using the value clarification technique (VCT) learning model in class V learning at SDN 002 Laggini. Indicators of social skills are: the ability to share or take turns, the ability to appreciate or respect, the ability to help, the ability to follow instructions and the ability to express opinions. This type of research is classroom action research. The subjects of this research were 28 class V students at SDN 002 Laggini. The cycle stage in research uses the steps of planning, implementation, observation, reflection. Data collection techniques were carried out using observation techniques. Data analysis techniques use quantitative and qualitative. The results of this research show that the value clarification technique (VCT) learning model can improve students' social skills. This can be shown by the observation results obtained in the first cycle of meeting I from 28 students. It was discovered that the social skills of students who were in the complete category reached 13 students (46%). The results of the first cycle of the second meeting of students who entered the complete category reached 15 students (54%). The results of cycle II of meeting I experienced an increase in students in the complete category reaching 20 students (71%). The results of the second cycle of the second meeting of students who entered the complete category reached 24 students (85%). Thus it can be concluded that through the application of the value clarification technique (VCT) learning model it can improve the social skills of class V students at SDN 002 Laggini.